Pharmacokinetics and metabolism of ketoconazole after single ocular instillation in Sprague-Dawley rats - Jiang Pu; Jingsong He; Ru Xue; Ruiqi Gao; Yaoming Yu; Wanyong Feng (International Association of Physical Chemists (IAPC), 2024)
Background and purpose: Ketoconazole is limited to its conditioned oral use due to hepatic toxicity. Its ocular eye drop administration may be an option for mycotic keratitis treatment. Therefore, it is necessary to explore its pharmacokinetic and metabolic profile via topical ocular administration. Experimental approach: Nine rats were dosed at 300 µg/rat via topical ocular administration, and sacrificed at 5, 30, and 120 min with 3 rats/timepoint. Plasma, cornea, retina, and vitreous humour samples were collected, processed, and analysed. Key results: Ketoconazole was quantified with a mean peak plasma concentration of 445 ng/mL at 5 min post-dose. In the rat ocular tissue, the mean ketoconazole concentration at 5 min post-dose was 423 μg/g in the cornea, 4.96 μg/g in the retina, and 1.19 μg/g in the vitreous humour, respectively. The mean ketoconazole concentration in each matrix decreased from 5 to 120 min. The mean ketoconazole concentration at 120 min was 38.4 ng/mL in plasma, and 8.36, 0.0944, and 0.116 μg/g in the cornea, retina, and vitreous humour, respectively. Pooled plasma, cornea, retina, and vitreous humour homogenates were used for metabolite identification. Nine metabolites were identified in rat plasma, and O-dealkylated metabolite (M3) and dehydrogenated metabolite (M11) were the top two, accounting for 5.0 and 5.8 % of the relative mass abundance. The metabolic pathways were O-dealkylation, mono-oxygenation, and dehydrogenation. Eleven metabolites were identified in the rat cornea, and two metabolites were identified in the rat retina and vitreous humour, respectively. The O-dealkylated and hydrogenated metabolite (M2) was a dominant metabolite in the cornea, retina, and vitreous humour, while M3 and M11 were the dominant metabolites in plasma. Conclusion: Ketoconazole was a dominant component (≥ 98.5 %) in the cornea, retina, and vitreous humour, having higher concentrations in cornea than in plasma. M2 was identified as a dominant metabolite (1.1 - 1.2 %) in the cornea, retina, while M3 (5.0 %) and M11 (5.8 %) were identified as dominant metabolites in the plasma.